Aleksandra Wolfgang – kobieta świata nauki i literatury I połowy XIX wieku - Kamilewicz-Rucińska, Danuta (Biuletyn Historii Wychowania, 2023)
The nineteenth century is known as a time of urbanization and industrialization, a time of new concepts, changes in the structure, cohesiveness and value system of contemporary societies. This kind of ideological and cultural eclecticism was not fully applicable in the process of shaping the perception of a woman. Women were still considered to be bereft of individuality while femininity was perceived as a negative trait and a manifestation of selfishness, with men’s dominant position conditioned by traditions, customs and the law. Aleksandra Tekla Sofia Wolfgang (1805–1861) was born to a family of Jan Fryderyk Wolfgang, a scientist, professor of pharmacy, pharmacology and chemistry, and Helena Aloiza Pacowski. Aleksandra made contribution to history by devoting her life to work, scientific and literary, thus giving up her family life. She began literary and scientific activity at the age of sixteen by writing articles, poems, and translating historical works (mostly from French) for the Vilnius press. She translated into Polish scientific works of her father and other world-renowned researchers. In the journal Dzieje Dobroczynności Krajowey i Zagraniczney [eng. The History of National and Foreign Charity] she was the only woman publishing under her own name. In the course of creating a herbarium to describe the flora of Samogitia, Jerzy Pabreż took advantage of some of Alexandra’s proposals to give new names to the plants. Aleksandra Wolfgang made her contribution to the development of botany in Lithuania by creating a herbarium, conducting experiments with plants in natural conditions and describing the surroundings. After her father’s death, she finished his Dictionary of Botanical Terms. She is also the author of the first publications in the Vilnius press about the history of education of the deaf and mute, which in 1830 resulted in the publication of a monograph entitled Rys historyczny usiłowań w uczeniu głuchoniemych i zakładów na ten cel przeznaczonych [Historical outline of education for the deaf and mute and the relevant establishments], written on behalf of all Lithuanians waiting for the support and benevolence of Alexandra Romanova, Empress of Russia. Aleksandra Wolfgang’s writing, especially her correspondence, shows the expressive, creative and scientific activity of Stefan Batory University during its closure by the tsar. For Alexandra Wolfgang, the life devoted to science and society was the simplest way to create and develop general good, which was acknowledged and emphasized by her contemporary scientists.